PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN DESTINASI HONEYMOON DI GILI MENO KABUPATEN LOMBOK UTARA - Roly Handika; I Made Murdana; Lalu Masyhudi; I Putu Gede; Uwi Martayadi (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2022)
Perception is the process by which a person selects, organizes, and interprets information inputs to create a meaningful overall picture. While the development of tourism is a destination whose development is determined in certain phases. The objectives to be achieved in this study are to determine the development of tourism in Gili Meno and to determine public perceptions of the development of honeymoon destinations in Gili Meno. In this study, the informants were village officials, pokdarwis leaders, and community leaders. In this study, the data collection methods used were observation, interviews, and documentation. The technique of determining the informants used purposive sampling. The initial step taken to find out the public's perception of the development of honeymoon destinations and tourism development in Gili Meno was by observing and conducting interviews with several informants. The results of this study indicate that the public's perception of honeymoon destinations is in the good category and the development of tourism in Gili Meno is in the development phase and has implications for the economy, environment, social and culture.